Multispectral object detection using 3D models cascade and region mutual information - Pong, Hon Keat. (2008)
The visual appearance of an object under natural lighting depends on its surface reflectance. However, there are situations when objects are to be viewed under non-visible light. Under such circumstances where reflectance information is not available, it is infeasible to use existing appearance-based object models which are based on surface reflectance. This thesis presents methods for detecting object instances within images, with efforts directed at developing methods that do not assume prior knowledge about reflectance information. We adopt the model based approach, in which a 3D model is used for detection by aligning it to image. An algorithm to speed up detection is also presented.